5.5 Indefinite integrals and sub rule

5.5 Indefinite integrals and sub rule - 1 5.5 Indefinite...

Info iconThis preview shows pages 1–4. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 1 5.5 Indefinite Integrals and Substitution Rule Fundamental Theorem of Calculus shows that antiderivatives are the keys to evaluation of definite integrals. In this section we study a technique of finding antiderivatives for functions that are not elementary, but have a special form. Example We begin by doing things backward: differentiate sin(x2 ) sin(x2 ) = Let’s write it again, but in slightly different way: sin(x2 ) = Integrating (or anti-differentiating), we get: sin(x2 ) dx = Thus u=x2 cos(x2 ) · 2x dx = Theorem Substitution Rule (u-Substitution) If u = g (x) is a and f is a function that is function whose range is an interval I , on I, then f g (x) · g (x)dx = where F is an antiderivative of f . Note: u-substitution is noting more than an inverse of the Chain Rule. Proof: d F (g (x)) = dx Integrating, we get: f (g (x))·g (x) dx = 2 Steps for u-substitution: • Choose your u. Separate the integrand into the parts that can be expressed in terms of u and a part that is a constant multiple of u • Make substitution and carry out integration • Substitute back for u to obtain the expression in terms of the original variable Example 1 Integrate: • 1 dx = ex • sin(7t) dt = • tan(s) ds = • ex tan(ex ) ln (cos(ex )) dx = 3 Example 2 Integrate: • • √ x2 x2 + 1 dx = • Example 3 To do √ x x2 + 1 dx = √ x3 x2 + 1 dx = Integrate: • et dt = 1 + et • tan−1 (x) dx = 1 + x2 4 Example 3 continued Integrate: 1 + 4x dx = 1 + 2 x + 4 x2 • √ • cos2 (2y + 3) sin(2y + 3) dy = • cot(z ) dz = In some cases, simplification needs to be done prior to application of u-substitution. Example 4 • 1+x dx = 1 + x2 • √ • √ x x + 1 dx = x2 dx = 1−x ...
View Full Document

This note was uploaded on 10/02/2011 for the course MATH 1206 taught by Professor Llhanks during the Fall '08 term at Virginia Tech.

Page1 / 4

5.5 Indefinite integrals and sub rule - 1 5.5 Indefinite...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online